Distinct characteristics of brain metastasis in lung adenocarcinoma: development of high-confidence cell lines - Jintao He; Zen-ichi Tanei; Dao-Sian Wu; Lei Wang; Yoshitaka Oda; Masumi Tsuda; Shinya Tanaka (Acta Neuropathologica Communications)
Abstract Lung cancer is a leading cause of cancer-related deaths worldwide, with brain metastasis occurring in approximately 30–55% of patients, particularly in lung adenocarcinoma. Due to the challenges in obtaining genuine brain metastasis tumor cells, researchers commonly use nude mouse models to establish brain metastasis cell lines, though traditional methods have limitations such as high costs, lengthy timeframes, and the need for specialized imaging equipment. To address these issues, we developed an improved approach by performing low cell number circulating intracranial injections (500–4000 cells) in nude mice, successfully establishing the H1975-BM1, BM2, and BM3 cell lines. Through RNA sequencing and bioinformatics analyses, we identified transcriptomic differences among these cell lines, revealing that H1975-BM1 cells primarily exhibit stem cell function and migration characteristics, while H1975-BM3 cells display enhanced chemotaxis, cell adhesion, and cytokine secretion associated with interactions. Experimental validation, including Transwell assays, CCK8, cell adhesion assays, and subcutaneous tumor implantation in nude mice, further confirmed these findings, with H1975-BM3 forming larger tumors and a more pronounced secretion cystic cavity. In conclusion, our improved methodology successfully established high-confidence brain metastasis lung adenocarcinoma cell lines, elucidating distinct transcriptomic and functional characteristics at different stages of brain metastasis progression.